An evaluation of two different methods for preoperative physical therapy information before abdominal surgery. (2nd April 2020) - Berthelsen, Ole; Wiklund, Malin; Säthil, Kerstin; Samulowitz, Anke; Fagevik Olsén, Monika
ABSTRACT: Introduction: Patients are often given preoperative information by a physical therapist with the aim of decreasing the risk of developing postoperative pulmonary complications and to facilitate recovery after major abdominal surgery. Studies are scarce about the effect. The aim of this study was to evaluate two different approaches for preoperative information. Design: Randomized controlled trial. Setting: University Hospital. Methods: This is a study comparing information by the Teach-Back Method (TBM) with traditional information. Fifty patients were included. They were randomized to either of the groups when attending the preoperative visit. A follow up by telephone was conducted a few days after. The patients were asked to recall the information received. A list of 29 statements was used to record whether participants recalled the given information. Results: The number of correct answers for the 29 statements was, in average 30.0% after TBM compared to 25.4% after traditional information (P = 0.179). In total, the patients recalled 27% of the information given. There were no significant differences between those who spontaneously gave positive feed-back regarding the information or not, those younger or older than 65 years of age, or for those who had read the written information. Conclusion: The patients recalled no more than 27% of the preoperative information and there were only minor and non-significant differences between the groups given information by TBM or traditionally. It is of importance to further discuss and evaluate when to inform the patients and which information to give when preparing patients prior to abdominal surgery.